Performance of male and female soccer players in field-based tests for screening the anterior cruciate ligament injury risk - Marques, V. B.; Oliveira, D. F.; de Borba Capaverde, V.; Michel, R. C.; Ribeiro-Alvares, J. B. A.; Baroni, B. M. (Sport Sciences for Health, 2023)
Background Female soccer players have a higher anterior cruciate ligament (ACL) injury rate than male players, possibly due to sex-specific intrinsic risk factors. The Landing Error Scoring System (LESS) and the Step-Down Test (SDT) have been used for screening the ACL injury risk, but the performance of adult soccer players in these field-based tests remains unclear.